1984
DOI: 10.1136/bmj.288.6433.1785
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone releasing factor: comparison of two analogues and demonstration of hypothalamic defect in growth hormone release after radiotherapy.

Abstract: Human pancreatic growth hormone releasing factor (hpGHRF(1-40)) stimulates the release of growth hormone in normal subjects and some patients with growth hormone deficiency. A study comparing the shorter chain amidated analogue hpGHRF(1-29) with an equivalent dose of hpGHRF(1-40) in seven normal subjects showed no significant difference In growth hormone response between the two preparations. Six

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

1985
1985
1999
1999

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…Radiation damage to the hypothalamus or pituitary probably involves a direct injury to these cells responsible for the hormonal secretion or an injury to the microvasculature inhibiting the transfer of the hypothalamic hormones to the pituitary. Many patients with radiation-induced GHD remain responsive to a bolus administration of growth hormone-releasing hormone, implying that the hypothalamus rather than the pituitary is the site of radiation damage [9][10][11][12][13][14]. Some clinical studies have indicated that the hypothalamus is more radiosensitive than the pituitary following lower dose irradiation of <40-50 Gy, whereas at higher doses of radiation there is evidence of both hypothalamic and pituitary dysfunction [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Radiation damage to the hypothalamus or pituitary probably involves a direct injury to these cells responsible for the hormonal secretion or an injury to the microvasculature inhibiting the transfer of the hypothalamic hormones to the pituitary. Many patients with radiation-induced GHD remain responsive to a bolus administration of growth hormone-releasing hormone, implying that the hypothalamus rather than the pituitary is the site of radiation damage [9][10][11][12][13][14]. Some clinical studies have indicated that the hypothalamus is more radiosensitive than the pituitary following lower dose irradiation of <40-50 Gy, whereas at higher doses of radiation there is evidence of both hypothalamic and pituitary dysfunction [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the CRF, deletion of C-terminal aminoacids of GRF does not reduce its biological activity [7,11,16]. Thus, the 29 N-terminal aminoacids of GRF (hpGRF 1-29) have the same biological activity as hpGRF 1-40 and hpGRF 1-44 [7,11].…”
Section: Physiology Of Crf and Grfmentioning
confidence: 95%
“…Thus, the 29 N-terminal aminoacids of GRF (hpGRF 1-29) have the same biological activity as hpGRF 1-40 and hpGRF 1-44 [7,11]. Since the pancreatic GRF 1-44 is identical to the hypothalamic GRF [9], the term human (h) GRF seems to be adequate.…”
Section: Physiology Of Crf and Grfmentioning
confidence: 99%
“…GHRH is a peptide which exists in the human hypothalamus in two forms, one consisting of 40, the other of 44 amino acids [20]. The growth hormone(GH)-releasing activity seems to be located in the 1-29-NH2-terminal amino acid sequence of GHRH, as judged from in vitro and in vivo studies with the synthetic sequences [13,14,18,22], This peptide has, however, not been identified in the hypothalamus. Attempts have been made to use GHRH in the diagnosis of impaired GH secretion [4], as well as to promote grot in GH-deficient children [12,23,27,28,31,33,36].…”
Section: Introductionmentioning
confidence: 99%